COVID-19 – CURRENT STATE OF MENTAL HEALTH WITH A REFERENCE TO HEALTH WORKERS - Latas, Milan; Pantović Stefanović , Maja; Đukić, Bojana (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: The COVID-19 pandemic has brought many problems and challenges to the medical profession, including psychiatry. These include the emergence of de novo disorders in the population, the worsening of the condition in previously diagnosed patients, but also problems in the mental functioning of health professionals, who were involved in the treatment of COVID-19 patients. Numerous international papers address these problems and challenges, as is the case with a large number of studies and papers published by Serbian researchers and experts in Serbian and international publications. Objective: The objective of the paper is to present research conducted in the Republic of Serbia related to the COVID-19 infection and its impact on mental health. Methods: This paper presents the results of Serbian research as well as expert opinions related to the COVID-19 infection and its impact on mental health. The basis for the preparation of this paper were publications of Serbian authors published mostly in international journals. These publications present the results of original studies, but also expert considerations related to the impact of the COVID-19 infection on mental health. Results: Previous research and extensive clinical practice in the Republic of Serbia show the existence of frequent and intensive problems related to mental health, resulting from the COVID-19 pandemic, present in both the general population and in specific populations, such as health workers and patients suffering from psychiatric disorders. Conclusion: Based on the presented results, the conclusion is that, in order to deal with this issue, a number of specialized institutions should be opened in the territory of the entire Republic of Serbia, where patients could find support and help for their problems.